2012
DOI: 10.13031/2013.42265
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic and Water Quality Models: Use, Calibration, and Validation

Abstract: To provide a common background and platform for consensual development of calibration and validation guidelines, model developers and/or expert users of the commonly used hydrologic and water quality models globally were invited to write technical articles recommending calibration and validation procedures specific to their model. This article introduces a special collection of 22 research articles that present and discuss calibration and validation concepts in detail for 25 hydrologic and water quality models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
201
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(208 citation statements)
references
References 31 publications
2
201
1
4
Order By: Relevance
“…Each topic is introduced with its description and relevance to model C/V before presenting key recommendations. The main components of these articles are: (1) a clear statement of why the topic is important with respect to model C/V, (2) a synthesis of the Moriasi et al (2012) special collection and other relevant literature with respect to the topic of focus, and (3) recommendations based on previous work summarized by Moriasi et al (2012) as well as personal experience. For some topics, a case study is provided to demonstrate the application of the topic-specific C/V recommendations.…”
Section: Summary Of Key Calibration and Validation Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each topic is introduced with its description and relevance to model C/V before presenting key recommendations. The main components of these articles are: (1) a clear statement of why the topic is important with respect to model C/V, (2) a synthesis of the Moriasi et al (2012) special collection and other relevant literature with respect to the topic of focus, and (3) recommendations based on previous work summarized by Moriasi et al (2012) as well as personal experience. For some topics, a case study is provided to demonstrate the application of the topic-specific C/V recommendations.…”
Section: Summary Of Key Calibration and Validation Topicsmentioning
confidence: 99%
“…Moriasi et al (2012) summarized model-specific C/V approaches for commonly used H/WQ models as part of the efforts initiated by ASABE in 2010 with the goal of developing calibration, validation, and documentation recommendations. The proposed follow-up phases were to identify critical C/V topics, synthesize the articles in the Moriasi et al (2012) special collection along with other relevant information from existing literature, and provide topic-specific recommendations. The authors of the present collection identified key C/V topics from the prior collection and addressed each in a separate article.…”
mentioning
confidence: 99%
“…Building on lessons learned in the previous RCA projects, the CEAP Cropland National Assessment used the best concepts from both the 1985 and 1997 assessments. A detailed field and hill slope assessment was performed using the Agricultural Policy/ Environmental eXtender model (APEX; Williams and Izaurralde 2006), while the Soil and Water Assessment Tool (SWAT; Arnold et al 1998Arnold et al , 2012 model was used to integrate the information at the watershed scale, using the US Geological Survey (USGS) developed eight-digit watersheds.…”
Section: Watershed Modeling and Usda Conservation Policy Planningmentioning
confidence: 99%
“…The SWAT model also provides several software tools, which include the pre-and post-processing software, automatic and manual calibration procedures, and an ArcGIS SWAT interface, as well as abundant theoretical and technical documentation, which consist of theoretical documentation, a user's manual and guide, a developer's manual, etc. [36][37][38]. Most of the software and documentation are conveniently and freely obtainable from [39].…”
Section: Swat (Soil and Water Assessment Tool) Modelmentioning
confidence: 99%